2019
DOI: 10.18203/2349-2902.isj20192983
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of serum C-reactive protein and D-lactate levels for early prediction of strangulation in intestinal obstruction

Abstract: Background: Intestinal obstruction is one of the commonest clinical problems encountered in surgical practice. One of the grave complications of intestinal obstruction is strangulation, which requires an emergency laparotomy for management. This study was conducted to emphasise the significance of early estimation of rise in serum C-reactive protein and D- lactate levels.Methods: Hospital based prospective study was performed on 50 patients admitted in J.L.N. Hospital, Ajmer in various surgical units with diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…LPS can promote the synthesis and secretion of inflammatory factors and then induce systemic inflammation. As a specific and sensitive indicator of gastric mucosal ischemia, FABP can reflect the condition of gastric mucosal ischemia and damage [ 19 , 20 ]. Lin et al [ 21 ] used transnasal intestinal obstruction catheterization to treat acute intestinal obstruction caused by Yellowstone, which can significantly control the disease progression and relieve abdominal distention and pain.…”
Section: Discussionmentioning
confidence: 99%
“…LPS can promote the synthesis and secretion of inflammatory factors and then induce systemic inflammation. As a specific and sensitive indicator of gastric mucosal ischemia, FABP can reflect the condition of gastric mucosal ischemia and damage [ 19 , 20 ]. Lin et al [ 21 ] used transnasal intestinal obstruction catheterization to treat acute intestinal obstruction caused by Yellowstone, which can significantly control the disease progression and relieve abdominal distention and pain.…”
Section: Discussionmentioning
confidence: 99%
“…CRP begins to rise in 3-6 h after inflammation, peaks in 30-60 h 17 . Studies suggested that CRP and lactate levels might help predict strangulation and make early decisions for surgery 18 .…”
Section: Discussionmentioning
confidence: 99%